Assessment of analgesic and antipyretic activity of traditional formula used in the treatment of seasonal infections - Parthiban, Kugalur Ganesan; Natesan, Senthil Kumar; Sekar, Ganesan; Mahalakshm, Krishnamoorthi (International Current Pharmaceutical Journal, 2013)
Traditional treatments and medicines are the main sometimes the only source of health care for millions of people living in rural areas of developing countries. The aim of the present study is to investigate the analgesic and antipyretic activity of individual plant extracts and poly-herbal formula [PHF] made in to liquid dosage form of three different doses in albino rats. The plant materials were extracted in boiling distilled water for six hours, filtered, concentrated and dried. The aqueous extracts were prepared in to poly-herbal liquid dosage form by using water, glycerol mixture and acacia 2% in three different preparation of varying extract doses.1ml of above preparations orally fed for investigation. Pentozocine and paracetamol was used as standard drugs respectively. For individual plants the extracts were suspended in 2% acacia solution and performed. The results of analgesic and anti-pyretic activity of PHF 1 and PHF 2 showed significant results (P<0.01 and P<0.05 respectively) and PHF3 did not show any significant results. In the individual plant extracts slightly significant activity (P<0.05) was observed. DOI: http://dx.doi.org/10.3329/icpj.v2i9.16075 International Current Pharmaceutical Journal, August 2013, 2(9): 143-147